Pengembangan LAPD Berbasis Kemampuan Berpikir Kritis Dengan Model Pembelajaran Inkuiri Pada Konten Asam Basa Yang Memuat Tiga Pertanyaan Keilmuan - Suyono; Windi Oktaviani (PendIPA Journal of Science Education, 2026)
This study aims to develop a Student Activity Worksheet (LAPD) to improve critical thinking skills through the inquiry learning model in Phase F of acid-base content by integrating three scientific questions. The feasibility of LAPD was evaluated based on three aspects, namely validity, practicality, and effectiveness. The development followed the ADDIE model, limited to the development stage. The pilot implementation was conducted on grade XI students at IPIEMS Senior High School Surabaya. The results of content and construct validation show that the LAPD is highly valid, with a mode score of 5 from three validators. The practicality analysis indicated a student response percentage of 95.59%, categorized as very practical. The effectiveness was determined based on the improvement in pretest and posttest scores of students critical thinking skills using the Wilcoxon Signed Rank Test. The test results showed a p-value (one-tailed) of 0.000 < 0.01, indicating that H0 was rejected and Ha was accepted. Furthermore, the analysis of students’ critical thinking practice assessment yielded a percentage of 93.13%. The analysis indicate that LAPD is feasible to be used to improve students’ critical thinking skills on acid-base content integrating three scientific questions through inquiry-based learning.